Spectacle wear and factors associated with non-compliance among children of 5-15 years - Mehnaz, Saira; Siddiqui, Ziya; Abedi, Ali Jafar; Ansari, Mohammad Athar (Indian Journal of Community Health, 2020)
Introduction: Refractive errors are the commonest cause of visual impairment in school children worldwide. They are correctible and after screening, spectacles can easily enhance vision. This can be achieved only when spectacles are used regularly. Objective: This study was conducted to study the compliance of spectacles wear among children and to determine the reasons associated with non-compliance. Methodology: 400 children in the age group of 5-15 years with refractive errors attending the eye OPD, using spectacles for more than three months were included. Spectacle wear and reasons of noncompliance were enquired. Data was analyzed to determine the factors associated with spectacle wear compliance. Results: Among 232 boys and 168 girls 142 were from rural and 258 from urban areas. 244(61%) children were compliant. Compliance was better in older children and those from urban areas. Children of educated parents and with power more than -1.0 D were more likely to be compliant. Main reason for not wearing spectacles was ‘lost or broken spectacles’ and dislike for spectacle. Conclusion: Counselling of parents, teachers and peers will be an effective step towards improvement of compliance of spectacles use.